Vaping topography, analysis of e-cigarette vapours and health risk assessment among current male users in selected population - Zainol Abidin, Najihah (2021)
Rising use of electronic cigarettes (EC) and limited data on its local vaping topography raise concerns and a challenge for a comprehensive health risk assessment to be done. This study aimed to estimate the non-carcinogenic health risks due to exposure to aluminium, chromium, iron, and copper as well as carcinogenic health risks from the exposure to formaldehyde, acetaldehyde, nickel, cadmium, and lead that are present in the EC vapours produced by locally-manufactured e-liquids. This study which was conducted in the Klang Valley, Selangor from February 2017 to April 2019 were divided into four substudies: i) a community survey on vaping topography, ii) chemical analysis of EC vapours, iii) daily exposure prediction modelling, and iv) Health Risk Assessment (HRA) of EC use. Data on vaping topography were gathered through purposive distribution of survey questionnaires to 226 tobacco users, including EC users. For the chemical analysis of the EC vapours produced by the ten local e-liquid samples, High-Performance Liquid Chromatography-Ultraviolet (HPLC-UV) was used to determine the concentrations of selected aldehydes whereas heavy metals content was quantified using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). Sub-study III predicted the range of the daily exposures potentially experienced by the EC users. The non-carcinogenic and carcinogenic health risks were estimated in sub-study IV based on the data obtained in substudy I to III. Out of the 226 tobacco users involved, 38% (n=86) were EC users who mostly (58.1%) preferred the third generation EC and purchased the product from the nearby vape shops. Majority of them used nicotinic e-liquid of 6 mg/mL with preference of creamy and fruity flavours. They reported usage of 50 puffs/day with two e-liquid bottles used up every month. The mean concentrations of formaldehyde, acetaldehyde, aluminium, chromium, iron, nickel, copper, cadmium, and lead were 4.31 ppm, 3.34 ppm, 0.126 ppm, 0.0258 ppm, 0.646 ppm, 0.520 ppm, 0.118 ppm, 0.00453 ppm, and 0.0288 ppm respectively when operated in low wattage setting. In high wattage setting, the concentrations were 7.04 ppm, 5.88 ppm, 0.205 ppm, 0.0323ppm, 1.51 ppm, 0.980 ppm, 0.0495 ppm, 0.00311 ppm, and 0.0256 ppm accordingly. The HRA estimated that the exposure to selected compounds in EC vapours may potentially result into 1 and 2 in every 10,000 EC user’s population to develop cancer in their lifetime. In sum, this study proves that exposures to aldehydes and heavy metals in EC vapours have measurable carcinogenic and noncarcinogenic health effects on its users with some were not disclosed and misled by the vigorous promotions of this product. The growing trend of EC users’ population among never-smokers and the rapid evolution of this product, continuous research focusing on local EC products and users is necessary to provide more scientifically-based evidences to authorities for comprehensive regulations on EC products to be formulated and implemented. Collaborative efforts from all stakeholders are vital to avert the initiation of tobacco use among never-smokers to facilitate the achievement of Malaysia as a tobacco-free nation by 2045.